Casting and Solidification of Light Alloys - Vorozhtsov, Alexander (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Investigation of the effect of casting and crystallization on the structure and properties of the resulting light alloys and, in particular, research connected with detailed analysis of the microstructure of light alloys obtained using various external influences of ultrasonic, vibration, magnetic, and mechanical processing on the casting and crystallization are discussed. Research on the study of introduction of additives (modifiers, reinforcers, including nanosized ones, etc.) into the melt during the crystallization process, the technological properties of casting (fluidity, segregation, shrinkage, etc.), the structure and physicomechanical properties of light alloys are also included.